2010
DOI: 10.1037/a0019494
|View full text |Cite
|
Sign up to set email alerts
|

Experimental effect of positive urgency on negative outcomes from risk taking and on increased alcohol consumption.

Abstract: The current pair of experimental studies sought to further validate the role of positive urgency (acting rashly when in an extreme positive emotional state) as a risk factor for impulsive and maladaptive behavior. Previous research has supported the use of emotion-based dispositions to rash action in predicting a wide range of maladaptive acts. However, that research was conducted in the field and relied on self-reported behavior, thus lacking tight experimental controls and direct observation of risky behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
87
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 30 publications
10
87
0
4
Order By: Relevance
“…While the mood induction used in Cyders et al (2010) appeared to be designed to induce a high activation positive mood, it was notable in the second study that a measure of elation derived from the Positive and Negative Affect Schedule (PANAS; Watson et al, 1988) showed a non-significant decrease from pre to post induction. Given the centrality of aroused emotion to the urgency construct (Cyders and Smith, 2008), it may be of benefit to specifically manipulate level of arousal in a positive mood induction, as suggested by others (Treloar and McCarthy, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the mood induction used in Cyders et al (2010) appeared to be designed to induce a high activation positive mood, it was notable in the second study that a measure of elation derived from the Positive and Negative Affect Schedule (PANAS; Watson et al, 1988) showed a non-significant decrease from pre to post induction. Given the centrality of aroused emotion to the urgency construct (Cyders and Smith, 2008), it may be of benefit to specifically manipulate level of arousal in a positive mood induction, as suggested by others (Treloar and McCarthy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The urgency traits have been shown to strongly predict a number of potentially risky behaviours Zapolski et al, 2009), and to also potentiate the relationship between affect and maladaptive actions (e.g. Cyders et al, 2010;Simons et al, 2010). Alcohol use has been one such potentially risky behaviour that has been examined in relation to the urgency traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of linear regression analyses based upon several selfreport questionnaire studies including a range of cognitive-emotional personal attributes have indicated that impulsiveness is predicted by negative affect, amotivation and depressiveness and counterpredicted by positive affect and internal locus of control in healthy volunteers (Palomo et al, 2008a, b; but see also Miller et al, 2009). Cyders et al have discussed the influence of positive urgency, acting rashly under extreme positive affect, and negative urgency as central risk factors for impulsive and maladaptive behavior (see also Cyders and Smith, 2008a, b;Cyders et al, , 2010Zapolsky et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The association between exposure to violence, alcohol, and drugs and psychosocial and behavioral outcomes among Mexican-American adolescents of low socioeconomic status E xposure to alcohol, violence, and drugs puts adolescents at high risk for developing current and future maladaptive and antisocial behaviors (Aldridge-Gerry et al, 2011;Coelho, 2012;Cyders et al, 2010;J. Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%